TOXIC EFFECTS OF WATER POLLUTION DUE TO LEATHER DYES ON WATER FAUNA - S.AFAQ (International Journal of Pharma and Bio Sciences, 2010)
The phospholipids are the principle compound of cell membrane and are essential for all vital cell processes. They are most important membrane building compound and are amphophilic molecules with unique physiochemical properties having both hydrophilic and hydrophobic parts to the molecules. The Phospholipid also plays a significant role in intracellular signaling. The phospholipid shows decreasing trend in present investigation after exposure to Bismarck brown and acid leather brown at different time intervals and at all three concentrations. However, the effect was more in acid leather brown exposure. Lipid peroxidation involves the direct reaction of oxygen and lipid to form free radical intermediate and to produce semi stable peroxide. Pathological free radical mechanism leading to lipid peroxidation and degradation of phospholipid with loss of membrane integrity are currently considered to be an important factor.